The Effectiveness of Acceptance and Commitment Group Therapy with a Look at Compassion Therapy in Cognitive Positive Emotion Regulation and Happiness in Patients with Major Depressive Disorder - Paktinatan, Elham; Chinaveh, Mahbobeh; Fereidooni, Samad (Applied Family Therapy Journal (AFTJ), 2022)
Aim: The present study aimed to examine the effectiveness of acceptance and commitment group therapy with a look at compassion therapy in cognitive emotion regulation and happiness in patients with major depressive disorder. Methods: The research method was quasi-experimental with a pretest-posttest design, a control group, and a three-month follow-up of the intervention therapy. Using the convenience sampling method, patients with major depressive disorder were selected from Jam, Siraf, Kankan, and Asalouyeh counties, and Pardis and Naft Jam towns in 2020, and were randomly assigned to an 8-member experimental group and an 8-member control group. After performing the pre-test, the experimental groups received acceptance and commitment group therapy based on compassion therapy for 8 sessions (90-minute sessions in 8 consecutive weeks). Research tools included the cognitive emotion regulation questionnaire by Garnefski et al. and Oxford Happiness Inventory. Data were analyzed using repeated-measures analysis of variance and SPSS25. Results: The acceptance and commitment group therapy with a look at compassion therapy increased cognitive positive emotion regulation and happiness in the experimental group in the post-test (P=0.05), and the effect was stable at the follow-up stage (P=0.05). Conclusion: The results indicated the effect of acceptance and commitment group therapy with a look at compassion therapy in patients with major depressive disorder, leading to higher cognitive positive emotion regulation and happiness, which should be always in main programs of counseling centers; hence, patients with major depressive disorder can reduce the rate of maladaptive behaviors by attending sessions and planning for objective and behavioral goals.